Prevalence of Drug-Drug Interaction in Hospitalized Patient in Basrah City; Southern of Iraq (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objectives: Although multiple drugs administrationmostly increase therapeutic effect, some combinations lead to adverse drug-drug interactions and increased morbidity. This study was designed to identify the types,frequency, severity, and significance of drug–drug interactions (DDIs)Methods: This retrospective cross-sectional study was conducted from September 2018 to February 2019 in Al-Fayha’a teaching hospital in Basrah, Iraq.The data of 186 patients were collected from hospital patients case sheets. The type and significance of DDIs were analyzed using “Medscape drug Interaction Checker.Results: At least one to two DDI are noticed in about three quarters of the patients, about 30% cases have three to nine DDIs and 15% of them have ten or more DDIs. According to their severity, there are 85 (11.5%) of serious or potent DDIs. The largest percentage of reported interactions 544 (73.5%) were moderate were close monitoring required. Out of 740documented DDIs,65.1% were pharmacodynamics and 19.5% were Pharmacokinetic interactions, in addition, there were 15.4%of DDIs due to Unknown mechanisms. Most of the major potential DDIs occur with the antibiotic ceftriaxone and blood thinning medications (heparin and warfarin).Conclusion: The findings of this study revealed a high prevalence of drug-drug interactions in hospitalized patients particularly in patients withcardiovascular disease. Potential DDIs in this study sufficiently high to alert health care providers to pay more attentions in order to prevent or decrease their adverse effects on patients.